Is there A Relationship between Route of Delivery, Perinatal Characteristics, and Neonatal Outcome in Preterm Birth? - (:unkn) unknown (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2018)
Background: Preterm birth is one of the most challenging problems in obstetric care and it is closely related to perinatal mortality and morbidity. The aim of the current study was to document our experience with preterm births and to analyze the association between perinatal variables and clinical outcomes. Methodology: In this retrospective study, data were derived from the medical records of 785 singleton preterm births delivered in the obstetrics and gynecology department of our institution. Variables under investigation were maternal and gestational ages, fetal gender, route of delivery (vaginal vs. cesarean section [C/S]), causes of preterm birth, birth weight, placental weight, umbilical cord length, and Apgar scores at the 1st and 5th min. Results: Pregnant women with advanced age (>= 35 years) were more likely to undergo C/S (P < 0.001). Apgar score at the 1st and 5th min was influenced significantly by gestational age (P < 0.001), newborn birth weight (P < 0.001), placental weight (P < 0.001), and umbilical cord length (P < 0.001). Infants delivered due to antepartum fetal distress indication had remarkably lower Apgar scores at the 1st min and the birth weight seemed to be positively correlated with Apgar scores at both 1st (P < 0.001) and 5th min (P < 0.001). Apgar scores both at the 1st and 5th min were positively correlated with placental weight (R: 0.239 and 0.231, respectively, and P < 0.001 for both) and length of umbilical cord (R: 0.228 and 0.211, respectively, and P < 0.001 for both). Conclusion: Advanced age pregnancies have higher C/S rates, but Apgar scores are significantly correlated with infant characteristics. Umbilical cord length and placental weight might be the new add-on predictors of postpartum well-being in premature infants.
Keywords: Apgar score; morbidity; neonatal; outcome; pregnancy; preterm birth; LOW APGAR SCORES; CESAREAN DELIVERY; SECTION; MORBIDITY; EPIDEMIOLOGY; ASSOCIATION; PREGNANCY; WEIGHT; IMPACT; RISK